PROVISION OF A LIBRARY FOR THE VILLAGERS - Mawardini, Annisa (Qardhul Hasan: Media Pengabdian kepada Masyarakat, 2017)
Library is one of the reading places which has tremendous benefits to increase knowledge. Through reading, people can be more qualified. In its development, the need for reading recognized as one of the basic human needs as a human right. However in its fulfillment sometimes shows some of the things that are not satisfactory, such as the unavailability of a library or reading park, the limitations of the existing books and funds in the procurement library, its influences to the lack of public interest in reading.